Current and Future Roles of Circular RNAs in Normal and Pathological Endometrium - Tu, Jiajie; Yang, Huan; Chen, Yu; Chen, Yu; Chen, He; Li, Zhe; Li, Lei; Zhang, Yuanyuan; Chen, Xiaochun; Yu, Zhiying (Frontiers in Endocrinology, 2021)
The uterine endometrium, which lines the mammalian uterus, is essential for embryo implantation. This lining undergoes significant changes during sexual and menstrual cycles. The endometrium is also associated with hormone-related diseases such as endometriosis and endometrial cancer. Circular RNAs (circRNAs) play a role in various biological processes. Recent studies have determined that circRNAs function in both normal and pathological endometrial environments. Here, we review high-throughput studies pertaining to circRNAs as well as individual circRNAs active in the endometrium, in order to explore the myriad functions of circRNAs in the endometrium and mechanisms underlying these functions, from panoramic and individual perspectives. Owing to their abundant expression, stability, and small size, circRNAs have displayed potential usefulness as diagnostic markers and treatment targets for endometrial-related diseases. Therefore, the specific role of circRNAs in the endometrium warrants systematic investigation in the future.